ANTIOXIDANT ROLE OF DJ-1 PROTEIN IN THE PATHOGENESIS OF PARKINSON'S DISEASE - Mussakhmetov, A.; Utepbergenov, D.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2022)
Parkinson's disease is a progressive age-related neurodegenerative disease, and oxidative stress is an important mediator in its pathogenesis. Loss of neurons in the midbrain region (Substantia nigra) causes dopamine deficiency and leads to the formation of intracellular inclusions containing α-synuclein aggregates. Both of these phenomena are considered neuropathological features of Parkinson's disease. Although the clinical diagnosis is based on the presence of bradykinesia and other major motor signs, Parkinson's disease is associated with many non-motor symptoms that contribute and complicate the disease. The underlying molecular pathogenesis involves several pathways and mechanisms: α-synuclein proteostasis, mitochondrial dysfunction, oxidative stress, disturbances in calcium homeostasis, and neuroinflammation. Mutations in the PARK7 gene resulting in loss of function of the encoded DJ-1 protein have been identified as the cause of one of several forms of the inherited form of Parkinson's disease. The DJ-1 protein is attributed the role of an antioxidant based on experiments in cellular model systems. The active site of DJ-1 contains a highly reactive cysteine residue (Cys106) which is oxidized under oxidative stress. It is assumed that Cys106 plays a critical role in the biological function of DJ-1, regulating antioxidant protection depending on the oxidation state of Cys106, i.e. acts as a sensor of oxidative stress. Thus, the level of oxidized DJ-1 (oxDJ-1) may serve as a possible biomarker of oxidative stress.